The Role of METTL3-Mediated N6-Methyladenosine (m6A) of JPH2 mRNA in Cyclophosphamide-Induced Cardiotoxicity - Zhu, Min; Liu, Yangong; Song, Yuanxiu; Zhang, Shiqin; Hang, Chengwen; Wu, Fujian; Lin, Xianjuan; Huang, Zenghui; Lan, Feng; Xu, Ming (Frontiers in Cardiovascular Medicine, 2021)
Cyclophosphamide (CYP)-induced cardiotoxicity is a common side effect of cancer treatment. Although it has received significant attention, the related mechanisms of CYP-induced cardiotoxicity remain largely unknown. In this study, we used cell and animal models to investigate the effect of CYP on cardiomyocytes. Our data demonstrated that CYP-induced a prolonged cardiac QT interval and electromechanical coupling time courses accompanied by JPH2 downregulation. Moreover, N6-methyladenosine (m6A) methylation sequencing and RNA sequencing suggested that CYP induced cardiotoxicity by dysregulating calcium signaling. Importantly, our results demonstrated that CYP induced an increase in the m6A level of JPH2 mRNA by upregulating methyltransferases METTL3, leading to the reduction of JPH2 expression levels, as well as increased field potential duration and action potential duration in cardiomyocytes. Our results revealed a novel mechanism for m6A methylation-dependent regulation of JPH2, which provides new strategies for the treatment and prevention of CYP-induced cardiotoxicity.